2002
DOI: 10.1095/biolreprod.102.004564
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimicrobial Peptide of Human Epididymal Duct Origin1

Abstract: HE2, a gene expressed specifically in human epididymis, gives rise to multiple mRNAs that encode a group of small cationic secretory peptides. Localization of HE2 within the defensin gene cluster and prediction that beta-defensin-like modules exist suggest that these peptides have antimicrobial activity and represent components of the innate epithelial defense system of the epididymal duct. Reverse transcription-polymerase chain reaction analysis confirmed the occurrence of eight human HE2-derived transcripts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…MUC15 overexpression in colorectal carcinoma cells enhances cell proliferation, cell extracellular matrix adhesion, colony-forming ability, and invasion (37). SPAG11B is a cationic secretory anti-microbial peptide expressed in human epididymis (38,39). FAM12B is an epididymal secretory protein (40,41) that has been found up-regulated in epididymides of nonobstructive azoospermic men (42).…”
Section: Discussionmentioning
confidence: 99%
“…MUC15 overexpression in colorectal carcinoma cells enhances cell proliferation, cell extracellular matrix adhesion, colony-forming ability, and invasion (37). SPAG11B is a cationic secretory anti-microbial peptide expressed in human epididymis (38,39). FAM12B is an epididymal secretory protein (40,41) that has been found up-regulated in epididymides of nonobstructive azoospermic men (42).…”
Section: Discussionmentioning
confidence: 99%
“…hBD3 was isolated originally from inflamed human skin, is inducibly expressed in various epithelia (18,22,25,47), and possesses a broad spectrum of potent bactericidal activities in a salt-insensitive manner against both gram-positive and gramnegative bacteria (18,22,25,46). Genomics studies have identified several new members of the ␤-defensin family (28,40,53). Recently, a circular form of antimicrobial peptides, called -defensins, has been characterized in macaques, while in humans all the genes encoding these peptides contain stop codons and are therefore likely to constitute expressed pseudogenes (12).…”
mentioning
confidence: 99%
“…These proteins have been shown to be processed when sperm cross the caput or corpus epididymis and to be involved in sperm fertility. We have also reported that several members of the matrix metalloproteases present in the epididymal fluid were activated from pro-to active forms after their transformation within the fluid (Metayer et al 2002a), and it has recently been demonstrated that an anti-microbial protein in human epididymal fluid and seminal plasma is processed in vivo and in vitro by furin (von Horsten et al 2002).…”
Section: Discussionmentioning
confidence: 93%